2021
DOI: 10.1088/1755-1315/845/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

The breeding of spring rapeseed and brown mustard for resistance to Fusarium blight

Abstract: During the growth season, the plants of rapeseed (Brassica napus L.) and brown mustard (Brassica juncea L.) are affected by various diseases: Fusarium blight, Verticillium blight, Alternaria blight, and others. The cultivation of rapeseed and mustard varieties resistant to diseases is a cost-effective and environmentally safe way to protect plants from diseases. The aim of the work was to evaluate the new breeding material of spring rapeseed and brown mustard for resistance to Fusarium blight in the form of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…To improve breeding programs, it is necessary to define the biochemical determinants responsible for the technological quality of brown mustard seeds as defined by French mustard manufacturers (texture, viscosity, color, stability, or syneresis). To date, sinigrin level, oil and protein contents, low erucic acid, and seed weight are used in breeding programs. Oil and protein contents are used by mustard manufacturers to assess the quality of the seed lots before processing, as they were empirically considered to be correlated with the mustard paste rheological behavior. A previous study showed significant linear correlations between the fat and protein contents of mustards and some parameters of rheological models .…”
Section: Introductionmentioning
confidence: 99%
“…To improve breeding programs, it is necessary to define the biochemical determinants responsible for the technological quality of brown mustard seeds as defined by French mustard manufacturers (texture, viscosity, color, stability, or syneresis). To date, sinigrin level, oil and protein contents, low erucic acid, and seed weight are used in breeding programs. Oil and protein contents are used by mustard manufacturers to assess the quality of the seed lots before processing, as they were empirically considered to be correlated with the mustard paste rheological behavior. A previous study showed significant linear correlations between the fat and protein contents of mustards and some parameters of rheological models .…”
Section: Introductionmentioning
confidence: 99%